Analisis Brand Awareness Terhadap Keputusan Pembelian pada Mehuli Kitchen Kabanjahe - Frandika Sitepu; Hendra Hendra; Dany Perdana Sitompul; Vinsensius Matondang (Yayasan Literasi Sains Indonesia, 2023)
This study was conducted to determine the effect of Brand Awareness on purchasing decisions at Mehuli Kitchen Kabanjahe. The type of research used in this study is quantitative, which is used to examine certain populations and samples. The study was conducted with a sample of 100 respondents, sampling using the slovin formula and data collection using research instruments. Data processing techniques using SPPS version 25. Data analysis techniques used are classical assumption test, multiple linear regression test and hypothesis test which includes t test, F test, and determination test. Based on the t test it is known that partially variable recall, recognition, and consumption significant effect on purchasing decisions at Mehuli kitchen Kabanjahe. And based on the F test that brand awareness variables include recall, recognition, purchase, and consumption simultaneously significant effect on purchasing decisions at Mehuli kitchen Kabanjahe with a percentage of influence of 66.1% and the remaining 33.9% influenced by other variables outside this study.